WATER QUALITY STUDY BASED ON MEIOFAUNA ABUNDANCE AND POLLUTION INDEX IN THE COASTAL ZONE OF LOSARI BEACH, MAKASSAR - Muhammad Sri Yusal; Muh Aris Marfai; Suwarno Hadisusanto; Nurul Khakhim (School of Postgraduate Studies, Diponegoro Univer, 2019)
The coastal zone of Losari Beach is located in a strategic position and rich in potential coastal resources, but the high density of human activities has decreased the quality of the surrounding waters.This study aimed to examine water quality based on meiofauna abundance and pollution index in the coastal zone of Losari Beach, Makassar. It employed a quantitative descriptive approach with purposive sampling method. The identified total meiofauna abundance was117,176 individuals/m2consisting of 138 species from 13 phyla. Ostracoda, olygochaeta, sarcomastigophora, ciliophora, and polychaetawere phyla with the highest abundance because of their high adaptability to polluted aquatic conditions. Meanwhile, tardigrada and aelosomatidaewere found in very low abundance because both phyla only thrive in pollution-free environments and have a pattern of high migration flow from one habitat to another. As for aelosomatidae, the habitat of its speciesis limitedto brackish or saline waters. A good-quality aquatic environment is a habitat for all benthic organisms and enables their even distribution. It explains the discovery of true and temporary meiofauna with uniform or even compositions in the bottom of the waters. The waters in the coastal zone of Losari Beach are heavily polluted. The stationslocated around the traditional Paotere harbor, hotels, restaurants, Losari Beach Platforms, the waste disposal outlets of Stella Maris Hospital, Fort Rotterdam canals, and Jeneberang River mouthhad very high pollution index. Some of these stations had low meiofauna abundance levels, and the poor water quality in their surroundings was caused by anthropogenic activity. Even though the area around TanjungMerdeka Beach had relatively low pollution index, it was categorized as severely contaminated because the index score was >10.